Strategi Pengembangan Proses Bisnis Di UPTD TPI Kecamatan Tanjung Tiram Kabupaten Batu Bara - Imelda Angglina Nasution; Tuti Sarma Sinaga; Nismah Panjaitan (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The Fish Auction Place (TPI) play a strategic role in supporting the distribution system of fishery product and imprroving the welfare of fishers. However, the auction function at TPI Tanjung Tiram has not operated optimally, as transactions continue to occur outside the designated auction area and operational management remains weak. This study aimas to analyze the business processes of the TPI and formulate appropriate development strategies. The research employes a qualitative approach with a case study design. Data collection techniques included interviews, direct observation, documentation, and the distribution of open ended questionnaires to fishery business actor. Data were analyzed using the VRIO frameworks to asses internl advantages and the PESTLE framework to examine exterbak environmental factors. The findings show that resource management is still suboptimal and exixsting facilities remain underutilized. Insight from the open ended questionnaires indicate the need fpr increased transaction tranparency, improvement of facilities, and enhanced us of technology, which significantly influences the performance of the TPI. This study cocludes that strengthening operational management is essential for improving the long term performance and sustainability of TPI Tanjung Tiram.